1974
DOI: 10.1037/h0036611
|View full text |Cite
|
Sign up to set email alerts
|

Children's psychological reactions to wartime stress.

Abstract: This research studied the psychological reactions of children in Israeli settlements subjected to frequent artillery shellings in the period following the 1967 Arab-Israeli War. It was found that the shelled children exhibited greater degree of locale patriotism, greater degree of covert aggression, and greater appreciation for the personality trait of courage than did the nonshelled controls. No differences between the shelled and the nonshelled groups emerged with respect to attitudes toward the war, desire … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

1988
1988
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(22 citation statements)
references
References 7 publications
2
20
0
Order By: Relevance
“…This may be attributed to the coping strategies developed by the adolescents who are chronically exposed to terrorism (Ziv, Kruglansky, & Shulman, 1974). Research conducted in Northern Ireland has also shown that children exposed to chronic violence demonstrate surprising resilience (McWhirter & Trew, 1981).…”
Section: Discussionmentioning
confidence: 99%
“…This may be attributed to the coping strategies developed by the adolescents who are chronically exposed to terrorism (Ziv, Kruglansky, & Shulman, 1974). Research conducted in Northern Ireland has also shown that children exposed to chronic violence demonstrate surprising resilience (McWhirter & Trew, 1981).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Baumgarten (1949) suggested that visible destruction, such as that endured by Warsaw, Poland, during WWII, carries existential implications that emerge indirectly in other activities, such as the production of destruction themes in artistic and political expressions, and that the destroyed buildings and infrastructure left behind by the war provided a lasting reminder of those deadly implications. Similarly, in a study conducted in Israeli settlements a year and half after the cessation of artillery shelling in the 1967 Arab-Israeli war (Ziv, Kruglanski, & Shulman, 1974), people living in shelled areas expressed more patriotism, covert aggression, and signs of courage than did those living in non-shelled areas.…”
Section: Introductionmentioning
confidence: 95%
“…In view of the hypothesis that psychological trauma frequently leads to phobias in young children (Gibson, 1989;Terr, 1991;Ziv, Kruglanski & Shulman, 1974), one would have predicted that children who saw their parents killed would show more irrational fears than the refugee children. Yet, the opposite relationship was found.…”
Section: Discussionmentioning
confidence: 99%